2012
DOI: 10.1186/1748-717x-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated partial breast irradiation using once-daily fractionation: analysis of 312 cases with four years median follow-up

Abstract: BackgroundThere are limited data on accelerated partial breast irradiation (APBI) using external beam techniques. Moreover, there are recent reports of increased fibrosis and unacceptable cosmesis with APBI using external beam with BID fractionation. We adopted a once daily regimen of APBI with fractionation similar to that shown to be effective in a Canadian randomized trial of whole breast irradiation. It is unclear whether patients with DCIS or invasive lobular carcinoma (ILC) are suitable for APBI.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These are similar or lower than several once-daily APBI series with 5year outcomes. [22][23][24][25] Shaiky et al, 26 with a median followup of 49 months, obtained IBTR of 1.9% and 1.0% of axillary failure. Goyal et al, 27 although only on 45 patients treated with once-daily APBI with 3D conformal radiation therapy technique, observed an IBTR of 0% at 3 years.…”
Section: Discussionmentioning
confidence: 97%
“…These are similar or lower than several once-daily APBI series with 5year outcomes. [22][23][24][25] Shaiky et al, 26 with a median followup of 49 months, obtained IBTR of 1.9% and 1.0% of axillary failure. Goyal et al, 27 although only on 45 patients treated with once-daily APBI with 3D conformal radiation therapy technique, observed an IBTR of 0% at 3 years.…”
Section: Discussionmentioning
confidence: 97%
“…However, it should be noted that all four patients with ILC who developed IBTR underwent preoperative MRI. Whereas some studies have shown a higher risk of IBTR for ILC [25, 29], other studies have failed to identify ILC as a significant predictor of IBTR after APBI [26, 30, 31]. The prospective experience with ILC is limited, as the histology accounts for less than 10% of the study population in select trials [10, 11], whereas others have excluded ILC cases altogether [6, 8, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Our own five-year follow-up experience at New York University, shows a 1% recurrence rate with 11% fair-to-poor cosmesis, 10 which is in line with many studies. 14,15 My opponent pointed out that the lack of defined prescription standards can result in large high dose regions which affect cosmesis. 4 This is the exact type of issue that is currently being studied and will eventually be solved.…”
Section: -3mentioning
confidence: 99%